THE INFLUENCE OF SOCIALIZATION, APPLICATION SYSTEM QUALITY, APPLICATION USAGE KNOWLEDGE, AND THE USE OF THE E-SAMSAT APPLICATION AS A MEDIATION VARIABLE ON MOTOR VEHICLE TAXPAYER COMPLIANCE (CASE STUDY IN BEKASI CITY) - Wilander, Jordy (DIPONEGORO UNIVERSITY, 2023)
This research was conducted as a case study in Bekasi City because revenue receipts, especially in vehicle taxes and the number of motorized vehicle owners, have increased significantly in 2018-2022. The government made an innovation in the form of an online application called